Rethinking the early Viking Age in the West - Griffiths, DW (Cambridge University Press, 2019)
The Viking Age in the West has long been perceived as a direct, colonising expansion of Scandinavian peoples, its causes most frequently sought within Scandinavia and linked together as concerted phenomena. This debate piece seeks to question these assumptions. Drawing on recent research that stresses the heterogeneity of Viking war-bands—and their early involvement in Francia and England—it proposes a ‘southern route’ through which Viking influence flowed towards the North Atlantic. The saga-attested early dominance of Norway over the Northern Isles is challenged, and attributed to a politicised re-writing of history four centuries later.